Cardioprotective use of melatonin causes gender-specific changes of vegetative cardiac control in a setting of constant illumination - H. O. Bezkorovaina; I. M. Klishch; M. R. Khara (Kazimierz Wielki University, 2020)
The aim of the work was to assess gender-specific differences in vegetative cardiac control with development of myocardial necrosis in a setting of constant illumination and use of melatonin. An experiment in mature laboratory breed albino rats of either sex simulated abnormal lighting regime. The simulation included keeping the animals for 10 days under constant illumination of 500 lux. On Day 11, myocardial necrosis (MN) was modeled by administering adrenaline (0.5 mg/kg intramuscularly); a follow-up electrocardiography was performed at 1 hour and 24 hours later to assess for heart rhythm variability. A half of animals was given melatonin 1 hour prior to MN modeling (5 mg/kg intraperitoneally). The animals kept under day/night balance were used as controls. The results have shown constant illumination to cause gender-specific changes in effects of vegetative nervous system on formation of heart rhythm in rats; the activity of the parasympathetic component increased in females and decreased in males. In females, the development of adrenaline-induced myocardial necrosis in a setting of constant illumination was accompanied by changes in cardiac interval (cardiointervalography) findings. The development of these changes with time was identical to that in day/night balance, with a more pronounced activity of the parasympathetic component and a synergetic enhancement of the sympathetic component. When exposed to constant illumination, males had a response different from that in day/night balance; their response to constant illumination was characterized by reduced activity of the parasympathetic component and by predominance of the sympathetic component. Cardioprotective use of melatonin was shown to increase parasympathetic tone compared to day/night balance; in males, this increase was evident at initiation of necrosis and in females, the increase was seen at the peak of necrotic foci formation in the myocardium.